The Local Job Multipliers of Green Industrialization - Federico Fabio Frattini; Francesco Vona; Filippo Bontadini; Italo Colantone (CESifo GmbH, 2025)
What are the job multipliers of the green industrialization? We tackle this question within EU regions over the period 2003-2017, building a novel measure of green manufacturing penetration that combines green production and regional employment data. We estimate local job multipliers of green penetration in a long-difference model, using a shift-share instrument that exploits plausibly exogenous changes in non-EU green innovation. We find that a 3-years change in green penetration per worker increases the employment-to-active population ratio by 0.11 pp. The effect is: persistent both in manufacturing and outside manufacturing; halved by agglomeration effects that increase the labour market tightness; stronger for workers with high and low-education; and present also in regions specialized in polluting industries. When focusing on large shocks in a staggered DiD design, we find ten times larger effects, particularly in earlier periods.
Keywords: J21; O14; R11; 330; green industrialisation; local job multipliers; employment effects of the green transition; shift-share IV design; difference-in-differences